Nivolumab causes focal muscular inflammation without electrophysiological or muscle magnetic resonance imaging findings. Issue 4 (19th June 2018) - Li, Fangzhou; Ayaki, Takashi; Ueda, Sakiho; Nagai, Hiroki; Murata, Kenya; Takahashi, Ryosuke
Abstract: A 62‐year‐old woman was admitted to our hospital complaining of bilateral shoulder muscle pain after nivolumab treatment. Her laboratory data disclosed elevated serum creatine kinase levels while the magnetic resonance imaging and the electromyography study were unremarkable. A left deltoid muscle biopsy was performed, and the evidence of focal inflammatory cell infiltration surrounding muscle fibers and upregulation of major histocompatibility complex class I was showed. Even mild and transient muscular symptoms after administration of nivolumab can represent immune‐mediated muscular inflammation.